2023
DOI: 10.3389/fspor.2023.1197793
|View full text |Cite
|
Sign up to set email alerts
|

Long-term development of performance, physiological, and training characteristics in a world-class female biathlete

Guro Strøm Solli,
Andrine Håstul Flom,
Rune Kjøsen Talsnes

Abstract: PurposeThe purpose of this study is to investigate the long-term development of performance, physiological, and training characteristics in a world-class female biathlete, with emphasis on differences between junior and senior athlete seasons.MethodsThe participant is a highly decorated female biathlete with 22 (10 gold) medals from international championships and 28 individual World Cup wins. Performance development (ages 17–33), physiological tests (ages 22–33), and day-to-day physical and shooting training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Therefore, it is logical that biathletes' training time may be reallocated for shooting practice, from time spent on other types of (physical) training.Total volume of annual strength training was significantly higher (~+24%) for XC skiers compared to biathletes (~51 vs 41 h•year -1 ). This finding aligns with recent research indicating that XC skiers perform almost double the volume of strength training compared with biathletes 6,21. Similar to previous studies2,9 , senior XC skiers performed more strength training during the preparatory phases, followed by decreased volumes towards CP.…”
supporting
confidence: 91%
“…Therefore, it is logical that biathletes' training time may be reallocated for shooting practice, from time spent on other types of (physical) training.Total volume of annual strength training was significantly higher (~+24%) for XC skiers compared to biathletes (~51 vs 41 h•year -1 ). This finding aligns with recent research indicating that XC skiers perform almost double the volume of strength training compared with biathletes 6,21. Similar to previous studies2,9 , senior XC skiers performed more strength training during the preparatory phases, followed by decreased volumes towards CP.…”
supporting
confidence: 91%
“…The total junior volume of ∼660 h discovered in this study is ∼25% higher than the volume during early senior age (21 years) reported for the most successful female XC-skier and male biathlete in history ( Solli et al, 2017 ; Schmitt et al, 2021 ). Consequently, the observed 35% increase in training volume ranks at the lower end of previous case studies on long-term development from early twenties to peak age in winter endurance atheletes, which ranged from 27% to 80% ( Solli et al, 2017 ; Rasdal et al, 2018 ; Schmitt et al, 2021 ; Solli et al, 2023 ). Given that no significant correlation emerged between junior training volume and generational aspects (year of birth) or junior age performance level (number of junior world championship medals) these factors can be ruled out as potential explanations.…”
Section: Discussionmentioning
confidence: 70%
“…Interestingly, the most pronounced changes in LIT from junior to senior age occurred during early preparation. We hypothesize that this is a consequence of natural progression and tolerance for higher training loads, as well as a higher degree of professionalization at senior age which is supported by a recent case study in biathlon (Solli et al, 2023). A high volume of training must be achieved throughout the year while ensuring that stress induced by training is at a sufficiently low level during competition season.…”
Section: Endurance Trainingmentioning
confidence: 79%
See 1 more Smart Citation